2019
DOI: 10.1097/ccm.0000000000003828
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Intake During Status Epilepticus and Outcome: A 5-Year Cohort Study

Abstract: Objectives: Recommendations regarding nutrition during status epilepticus are lacking, and it is unclear whether restriction of calorie intake would result in beneficial effects or potential harm. We thus aimed to investigate associations between daily calorie intake and outcome in adult status epilepticus patients deriving from a 5-year cohort with a systematic and prospective collection of nutritional data. Design: Retrospective observational study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…As in our previous studies and according to the recent guidelines for the evaluation and management of SE, SE was defined as clinical and EEG evidence of seizure activity that lasted at least 5 minutes or as a series of epileptic seizures without complete clinical recovery between. 6 Types of SE (as described in previous studies [18][19][20][21] ) were assessed from the digital EEG databases of both centers or from prehospital and emergency department reports if EEG was not informative or not performed. SE types were defined as recommended by the current guidelines of the International League Against Epilepsy (i.e., focal nonconvulsive SE without coma [with or without altered consciousness and absence SE], SE with motor symptoms [myoclonic and convulsive], and nonconvulsive SE with coma).…”
Section: Definition and Classification Of Se Types And Durationmentioning
confidence: 99%
“…As in our previous studies and according to the recent guidelines for the evaluation and management of SE, SE was defined as clinical and EEG evidence of seizure activity that lasted at least 5 minutes or as a series of epileptic seizures without complete clinical recovery between. 6 Types of SE (as described in previous studies [18][19][20][21] ) were assessed from the digital EEG databases of both centers or from prehospital and emergency department reports if EEG was not informative or not performed. SE types were defined as recommended by the current guidelines of the International League Against Epilepsy (i.e., focal nonconvulsive SE without coma [with or without altered consciousness and absence SE], SE with motor symptoms [myoclonic and convulsive], and nonconvulsive SE with coma).…”
Section: Definition and Classification Of Se Types And Durationmentioning
confidence: 99%
“…As described earlier (14,(35)(36)(37)(38), SE duration was defined as the time between the first clinical and/or electroencephalographic evidence of seizure and seizure termination on electroencephalograph. As our monitoring unit used two different electroencephalographic strategies, such as continuous or spot electroencephalographs of greater than or equal to 30 minutes every 12 hours, SE duration represents a 12-hour approximation.…”
Section: Se Definition Cassification and Durationmentioning
confidence: 99%
“…This therapy should be started and monitored by a physician experienced in KD, or a nutritional expert, to avoid electrolyte or vitamin imbalance or hypoglycemia, and standardized protocols should be followed [157]. A recent study on the nutritional state in SE showed that the induction of ketogenesis might improve treatment outcomes and will surely stimulate the conduct of further research into the adoption of KD in SE [183]. The use and benefits of MgSO 4 in non-eclamptic RSE are controversially discussed within the field [26,184] and are only supported by weak evidence (level 5, grade D).…”
Section: Discussionmentioning
confidence: 99%